Nanoformulation of Antibacterial Antibiotics Cefpirome with Biocompatible Polymeric Nanoparticles and Evaluation for the Improved Antibacterial Activity and Nontarget Toxicity Studies - Namasivayam, S. Karthick Raja (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Purpose: Nanotechnology principles are extensively utilized in the development of various drugs which exhibit the improved spectrum of activity with the less side effects. Among the various nanoparticles (NPs), protein-based nanomaterial gains recent attention because of the high rate of efficacy, delivery, and less side effects. In this study, the antibacterial antibiotics cefpirome has been formulated with biocompatible ovalbumin (OVA) NPs and the nanodrug conjugate was evaluated against improved antibacterial activity, in vitro control release and nontarget toxicity against Vero cells and blood cells. Materials and Methods: The methods for the preparation of phycocyanin functionalized OVA NPs were optimized with various parameters adapting coacervation technique. The nanodrug conjugate prepared using the optimized condition was characterized using electron microscopy studies, Fourier transform infrared spectroscopy and in vitro controlled drug release by continuous dialysis method, antibacterial activity against human pathogenic bacterial strains by well diffusion, liquid colorimetric assays, and biofilm inhibition assays. Nontarget toxicity study was conducted by determination of cytotoxicity against Vero cell line and human peripheral blood cells under laboratory condition. Results: Phycocyanin functionalized nanodrug conjugate was prepared under optimum condition characterized by electron microscopy studies reveals nanosphere is in the range of 100-200 nm. The drug loading efficiency and entrapment efficiency were found to be 85.0% and 90.5%. The in vitro drug release profile showed a steady rate of release and maximum release of 99.0% during 20 h. Antibacterial activity against human pathogenic bacteria showed improved spectrum of activity against all the tested pathogenic bacteria as dose-dependent manner. Microtiter plate and nitrocellulose membrane assay were adapted to study the biofilm inhibition of pathogenic bacteria which revealed all the tested bacterial biofilm was highly inhibited in both the tested assays as concentration-dependent manner. Effect of drug conjugate on dynamic growth curve of tested bacteria also showed the drastic reduction of growth inhibition. The antibacterial activity of nanodrug conjugate was found to be retained all the tested temperature against all the tested bacterial organism. Nontarget toxicity studies showed there was no distinct toxic effect on Vero and blood cells. Conclusion: Effective inhibition of pathogenic bacteria and best biocompatibility of nanoformulated cefpirome would suggest the possible utilization of the formulation as an antibacterial agent to fight against human pathogenic bacteria in modern medicine.